Estudo experimental da transferência de forças de cisalhamento em pisos mistos de pequena altura com perfil celular de aço e lajes alveolares pré-fabricadas de concreto - Coldebella, Gustavo (Universidade Federal de São Carlos, 2019)
Alveolar steel beams and precast hollow core concrete slabs on slim floor systems is a very innovative association and brings as main characteristics the ability to overcome large spans and high degree of industrialization, resulting in a light and efficient system from a structural and constructive point of view. However, this association is only achieved when the joint behavior between steel and concrete occurs, with the transfer of forces between the elements. In this context, the objective of the present work is to study the mechanisms responsible for the transfer of shear forces at the steel-concrete interface (cellular beam-hollow core slab). It was evaluated if the reinforcing bars that cross the profile and slab openings and are surrounded by the concrete contribute to the transfer of forces between the elements of the slim floor. The influence of the change of the diameter of the steel bars passing through the openings and the compressive strength of the concrete was also evaluated. For this purpose, six physical models subjected to a push-out test were used: two pilot models and four definitive. It was observed that the presence of the steel bar contributes significantly to both the strength of the bonding and to reducing the steel-concrete relative slip. While the non-rod models presented a post-peak behavior with a strong drop of resistant capacity, in the models with steel bars the behavior was quite ductile presenting residual post-peak capacity very close to the maximum strength resisted. The change in bar diameter and concrete strength influenced both behavior and strength. It was observed that regardless of the presence of steel bar, until the concrete dowel breaking force, the behavior of the models with and without bar is almost identical. The experimental results of applied maximum force were compared to analytical models proposed by other researchers. However, none of the models found in the literature were able to satisfactorily represent the resistant capacity of the models with and without steel bar; only in isolated cases there was a good correlation, and adjustments were necessary in the analytical models in the literature. A good estimate of the theoretical results was obtained using the friction-shear theory.
Experimental study of the shear forces transfer in slim floor systems with steel cellular beam and precast hollow core concrete slabs
Keywords: Piso misto de pequena altura; Laje alveolar de concreto; Viga celular de aço; Cisalhamento direto; Pino de concreto; Slim floor system; Hollow core concrete slab; Steel cellular beam; Push-out; Concrete dowel; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS